Mobile Robot Indoor Localization Using Color-Coded Beacons and a Depth Camera - Basheer, Mawj Mohammed; Çavaş, Mehmet; Qasim, Mohammed (My University, 2022)
This paper aims to design and implement an indoor localization method for mobile robots based on trilateration technique, Color Code signatures (CCs) as artificial passive beacons, and a depth camera. The artificial passive beacons are designed as three disks positioned one on top of the other’s with different sizes and colors (primary colors only, RGB). The three disks share the same center. The designed beacons are placed on the ceiling to be visible from most locations within the room. The robot's model, controller, and localization method are implemented and evaluated inside the CoppeliaSim environment. The simulation results show that the CCs detecting algorithm enables the robot to discover the designed beacons, achieve an accurate localization and reach the target
Keywords: CoppeliaSim program; Omnidirectional robot; localization; Trilateration.